The components of communication systems in universities: their influence on academic work life. Issue 1 (2nd January 2018) - Uslu, Baris
Abstract : This research aimed to identify the components of communication systems in universities and to explore their influence on academic life. To collect data, interviews were carried out with academics from Australian universities. Thematic descriptive and content analyses were performed on the data-set. Analyses showed that the human relations unit, deanship office, academic board, newsletters, academic and public events, tea/coffee/lunch meetings, social activities and celebrations are common formal and informal channels of communication in universities. Academic support mechanisms also provide various communication opportunities such as professional interactions during staff training, collegial evaluation on grant proposals, and intellectual discussions at public events. Access to top management and mentoring between senior and junior academics are other important kinds of communication. The results revealed that good communication systems are an essential component of a participative, collaborative and interdisciplinary work environment, and as such a positive environment noticeably contributes to academics' individual and collective productivity.